Power Generation from Human Leukocytes/Lymphocytes in Mammalian Biofuel Cell - Güray Güven; Pablo Lozano-Sanchez; Arcan Güven (International Journal of Electrochemistry)
Alternative to batteries power sources is needed for the human implants of the future that tend to be less invasive and more integrated to human biology and physiology. Human metabolism could be exploited for the generation of power, but mammalian cells protect their energy production apparatus from external electrochemical scavengers. We report here evidence that, in the case of white blood cells, chemical energy can be harvested directly on an electrode as electricity in fuel cells whose stability is roughly parallel to the viability of cells in vitro. Electrochemical activity of human leukocytes immobilized on modified carbon mesh electrodes was investigated by cyclic voltammetry. Oxidation peaks at 0.33 V versus Ag/AgCl were observed. An open-circuit potential of 0.44 V was recorded between anode and cathode compartments where the biofuel cell potential operating under an external load of 5 kΩ was below 0.35 V. Average power outputs of 10 μW (2.4×10-6 μW/cell) were increased to 15 μW by the activation of white blood cells. Power densities of 1.5 μW cm−2 for lower than physiological cell concentrations are low for most of today’s implants, but possibility of cell immobilization allows a positive outlook for the future utility of the reported findings.